MANAJEMEN SARANA DAN PRASARANA DALAM MENINGKATKAN EFEKTIVITAS MEDIA PEMBELAJARAN SISWA – SISWI DI MADRASAH TSANAWIYAH ANWARUL HASANIYYAH (ANWAHA) KABUPATEN TABALONG - Muhammad Rifki; Rahmat. I; Syabri Syabri; Syahrani Syahrani (EDUCATIONAL JOURNAL : General and Specific Research, 2023)
Facilities, infrastructure, technology and textbooks are important factors in the learning process. Facilities and Infrastructure Standards are national education standards relating to minimum criteria for classrooms, sports halls, places of worship, libraries, laboratories, seminars, playgrounds, places for creativity and entertainment as well as other learning resources needed to support the learning process, including their use. The use of information technology allows the learning process to shift from passive absorption of learning material to conscious awareness, so that the learning process becomes more interesting and effective. Student-centered curriculum design must adapt students' abilities, including skills, knowledge and attitudes, to their talents, interests and development, focus attention on students, determine learning models, develop teaching materials, determine the learning process, pay attention to learning objectives. Management of educational facilities and infrastructure to improve the quality of learning must start from planning, procurement, maintenance, disposal and monitoring. Adequate facilities and infrastructure, technology and textbooks can help improve the quality of education and increase student achievement in the fields of sports, science and technology. This research aims to analyze the role of facilities and infrastructure management in increasing the effectiveness of learning media for students at Madrasah Tsanawiyah Anwarul Hasaniyyah (ANWAHA) Tabalong Regency. Good management of facilities and infrastructure in schools is very important to create a conducive learning environment. The research method used is a case study by collecting data through observation, interviews and document analysis. The research results show that the management of facilities and infrastructure at Madrasah Tsanawiyah Anwarul Hasaniyyah has made a positive contribution to the effectiveness of student learning media. Adequate and well-maintained facilities create an environment that supports the learning process. In addition, the management of technology and sophisticated learning tools has helped improve the quality of teaching. This research underlines the important role of facilities and infrastructure management in increasing the effectiveness of learning in madrasas. These findings can be a basis for decision making at Madrasah Tsanawiyah Anwarul Hasaniyyah and other madrasas to continue to improve and manage facilities and infrastructure well in order to improve the quality of education.